Tá na hora de cocô e cadê o meu cocô? - Silva, Marli Felício Santana; Henrique, Maria de Fatima Oliveira; Firmino, Valeria Aparecida; Silvério, Agda Rodrigues Rios; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf